APPROACHES TO THE TREATMENT OF METASTATIC BREAST CANCER (Texas Journal of Medical Science, 2024)
Progress in the treatment of this disease, metastatic dissemination is still considered an inclusive condition. In this lecture will be considered questions of «non-standard» therapy, which may be included in our practice in the future